Validity of the use of a fixed point for intracycle velocity calculations in swimming - Psycharakis, S. G.; Sanders, R. H. (Journal of Science and Medicine in Sport, 2009)
The intracycle velocity (V) of a fixed point on a swimmer's body, usually the hip, is frequently calculated as a direct indication of the intracycle V of the centre of mass (CM). The purpose of this study was to examine whether the intracycle V of the hip reflects accurately the intracycle V of the CM in freestyle swimming. One stroke cycle was analysed for ten swimmers performing a maximum freestyle swim. The magnitude of differences between CM and hip values was calculated for the instantaneous V values, the intracycle V fluctuation (Vfluc) and the magnitude and timing of appearance of maximum (Vmax) and minimum intracycle V (Vmin). Large differences were found in all variables, with the use of the hip for V calculations overestimating significantly Vmax and underestimating significantly Vmin and Vfluc of the CM (p <= 0.001). The results of this study showed that the hip motion should not be used as an indication of the intracycle CM motion in freestyle swimming.